2019
DOI: 10.3390/su11113053
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Environmental Efficiency Assessment of Industrial Water Pollution

Abstract: In the face of severe water pollution, all provinces and cities in China have actively invested in water environment management funds driven by the goals of national energy conservation and emissions reduction. However, due to differences in natural environment, economic and technological levels, industrial structure, and other aspects in provinces and cities, their water environment management effects are also different across time and space. Under economic development and environmental regulation policies, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 26 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…An empirical analysis was organized to examine the primary factors that cause performance loss in energy-saving and emissions reduction (Wang et al, 2015). Zhang et al used dynamic SBM models to evaluate the overall efficiency of decision-making units (DMUs) for the whole term period, as well as the term period efficiencies in industrial water pollution (Zhang et al, 2019). This proposed dynamic DEA model incorporates carryover activities and helps measure a period's specific efficiency based on long-term optimization during the whole period.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…An empirical analysis was organized to examine the primary factors that cause performance loss in energy-saving and emissions reduction (Wang et al, 2015). Zhang et al used dynamic SBM models to evaluate the overall efficiency of decision-making units (DMUs) for the whole term period, as well as the term period efficiencies in industrial water pollution (Zhang et al, 2019). This proposed dynamic DEA model incorporates carryover activities and helps measure a period's specific efficiency based on long-term optimization during the whole period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…About a decade ago, Franks, Brereton, and Moran and Mamurekli evaluated the environmental cumulative effects of coal resource development and utilization and suggested that the authorities involved should play significant roles in improving impact assessment and institutional formulation (Franks et al, 2010;Mamurekli, 2010). Using evidence from China's coal sector, a recent study by Zhang et al addressed the relationship of energy-price regulations and price fluctuations by building simultaneous equations for coal price and coal supply and constructing a forward-looking coefficient to evaluate different coal pricing policies from 2008 to 2016 (Zhang et al, 2019). Sueyoshi and Yuan focused on the unintended consequences of China's coal capacity cut policy and revealed that the capacity cut policy should be differentiated across regions due to the fragmentation of the coal markets, unbalanced distribution of resources, and a mismatch between production and demand centers (Sueyoshi and Yuan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many scholars often use atmospheric pollutant emissions as input indicators in empirical research to conduct empirical measures of atmospheric environmental performance [21,22], atmospheric environmental efficiency [11,19,23,24] and measure and analysis of atmospheric pollution emission efficiency [25][26][27]. From the evaluation method, the environmental efficiency measure based on the data envelopment analysis (DEA) method and its improved model is widely used [28][29][30]. After Charnes et al proposed the DEA method in 1978 [31], from the traditional radial framework to the non-radial framework considering slack variables, different scholars have proposed improved models such as the SBM (Slacks-Based Measure)-DEA model [32,33], Super-SBM model [10,34,35], and non-radial directional distance function (NRDDF) DEA model [11,25].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [27] investigated the dynamic carbon emissions performance of China's industrial sectors using the Malmquist-type index. Zhang et al [28] used the dynamic slacks-based measure (SBM) model to assess the environmental efficiency of industrial water pollution. More details of dynamic efficiency evaluations can be found in Chen and Golley [29] and Yao et al [30].…”
Section: Introductionmentioning
confidence: 99%